INITIAL IMPACT OF THE COVID-19 PANDEMIC ON THE CARE PROFILE FOR CRITICALLY-ILL PATIENTS ON HEMODIALYSIS - Claudia Gallota; Tatiana Garcia Viana; Fabiana da Silva Augusto; Regina Elena Genovese; Carlos Alberto Balda; Ieda Aparecida Carneiro (Cogitare Enfermagem)
Objective: to compare the care profile for critically-ill patients on hemodialysis before and during the COVID-19 pandemic.